Wall associated kinases (WAKs) gene family in tomato (Solanum lycopersicum): Insights into plant immunity - Kurt, Firat; Kurt, Baris; Filiz, Ertugrul (Elsevier, 2020)
Wall-associated kinases (WAKs), a subgroup of receptor-like kinases (RLKs), are localized on the cell wall and have roles in pathogen recognition and signal transduction in plants due to their interactions with pectin molecules. In this study, it was aimed at characterizing WAK genes in tomato (Solanum lycopersicum) using bioinformatics approaches. In this respect, all SlWAKs were identified as RD-kinases and all motifs in eukaryotic protein kinase (ePK) subdomains in SlWAKs were determined. Motif, sequence, and protein structure analyses showed that Solyc07g007020.2 and Solyc09g014740.2 are more distinctive proteins among SlWAKs suggesting that they may be involved in very specific pathways in plant defense system and may have different ligand selectivity. Other than that, we found that miRNAs silencing SlWAK genes are involved in various pathways and controlled with complex biological processes. Docking analyses showed that oligomeric pectin has higher binding affinity to SlWAK1. The findings are important for plant protection studies aiming at identifying roles of different WAKs in plant immune system, particularly in tomato.
KURT, FIRAT/0000-0003-0172-1953; Filiz, Ertugrul/0000-0001-9636-6389; KURT, BARIS/0000-0002-1406-0915
Keywords: Wall-associated kinases (WAKs); Pathogen; Immunity; Bioinformatics; Oligomer pectin; Docking